Factors influence the public’s willingness to purchase life insurance policy / Siti Munirah Sarif - Sarif, Siti Munirah (2010)
This study is designed to identify the factors that influence public’s willingness to purchase life insurance. Awareness, personal risk and income level are the independent variables. The dependent variable is willingness of public to purchase life insurance policy. The objective of the study are to determine the level of willingness of public to purchase life insurance, secondly to identify the significant relationship between the factors that influences the public’s willingness to purchase life insurance and thirdly to identify the key factors that influence the public’s willingness to purchase life insurance. The data set in this study are collected from the resident in Damansara through questionnaires. 100 respondents in that area had become the sample in this study by answering the questionnaires that randomly distributed. Three hypotheses were developed and tested using Pearson Chi Square assisted by Statistical Package for Social Science (SPSS) Version 16.0. The findings indicate there is a high level of public’s willingness to purchase life insurance. Besides, between the three variables, awareness has no significant relationship with the factors that influence the public’s willingness to purchase life insurance policy, while personal risks and income level shows the significant relationship and income level become the most contributing factor that influence the public’s willingness to purchase life insurance policy. There are also several recommendations that researcher suggest based on the findings found.